The effectiveness of young environmental scientist program among secondary school students in Terengganu, Malaysia - Auwalu, Rabiu Ali; Mohd Ekhwan, Toriman; Muhammad Barzani, Gasim; Hafizan, Juahir (2015)
The purpose of this research was to investigate the environmental awareness level, attitude of students towards environment and their interest in learning science. The sample used for this research comprises both boys and girls students of Form Four. A total of one hundred (100) students were randomly selected. The data was collected using the Environmental Awareness Scale prepared by the researcher. It was then analyzed using descriptive statistics, t-test and Karl Pearson’s coefficient of correlation. The result revealed that, the level of environmental awareness of students is high but moderate interest in learning science. The researcher concluded that Young Environmental Scientist (YES) Program should be adopted by all secondary schools in Terengganu, Malaysia and should be infused in the curriculum.